Investigation of aluminum nitrate as a set retarder of magnesium potassium phosphate cement: Mechanisms involved in diluted suspension. (December 2021) - Cau Dit Coumes, Céline; Rousselet, Angélique; Xu, Biwan; Mercier, Cyrille Albert; Gauffinet, Sandrine
Abstract: In this study, the influence of aluminum nitrate on the hydration process of magnesium potassium phosphate (MKP) cement was investigated experimentally and through thermodynamic modelling using diluted systems with Mg/PO4 molar ratio and water-to-cement ratio of 1 and 100 respectively. Three processes contributed to retard cement hydration: the acidic nature of aluminum nitrate which reduced the initial pH of the solution by two units, the early precipitation of a taranakite-like amorphous potassium aluminophosphate, which reduced the aqueous phosphate and potassium concentrations, and a salt effect due to the presence of soluble nitrate. Precipitation of potassium-containing magnesium phosphate hydrates, like Mg2 KH(PO4 )2 ⋅15H2 O and K-struvite, was prohibited, whereas precipitation of newberyite and cattiite was delayed. Furthermore, the modelled phase development with ongoing cement hydration agreed rather well with the experimental findings.